DOMINASI WORD OF MOUTH DALAM MEMBENTUK KEPUTUSAN PEMBELIAN PADA UMKM BAKSO MBAH MO SAMOTA - Agus Santoso; Adilla Nisaela Khairamiranti (Jurnal Ekonomi dan Bisnis Indonesia, 2026)
This study aims to analyze the influence of digital marketing, influencer, and word of mouth (WOM) on purchase decisions at Bakso Mbah Mo Samota MSME in Sumbawa. This research used a quantitative, associative approach. The population consisted of consumers who had purchased products from Bakso Mbah Mo Samota. The sampling technique used was non-probability purposive sampling, yielding 150 respondents. Data analysis was conducted using multiple linear regression analysis. The results showed that digital marketing and influencer variables did not have a significant effect on purchase decisions.Meanwhile, word of mouth had a positive and significant effect on purchase decisions. Simultaneously, digital marketing, influencer, and word of mouth significantly affected purchase decisions. The findings indicate that recommendations and consumer experiences have a greater influence on purchase decisions in local culinary businesses than digital promotional activities. Consumers tend to rely more on direct experience and social recommendations from their surroundings when making purchasing decisions.